Datified cartographies. An artistic proposal for data visualization to highlight environmental emergencies (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2019)
The text analyzes how data visualization can be considered as an artistic methodology that helps to highlight different environmental emergencies in today's society, focusing on the case study of forest fires. Some datified cartographies that, using new technologies and the installation and multimedia artistic process, play an immersive role and new visual possibilities for the field of contemporary artistic experimentation.
Keywords: Data visualization; cartographies; enviromental emergencies; Technology; Artistic methodology